Dosis de fertilizante orgánico y sus efectos en el cultivo de Lycopersicum esculentum Mill, tomate Var. Rio grande, Zungarococha-Loreto. 2022 - Quispe Melgar, Oliver Handersson (2023)
The research was developed with the certainty of finding answers in the agronomic characteristics and yield of the tomato to the application of the organic fertilizer "protowallpa", using doses of 10, 20, 30 and 40 t / ha, in a clay loam soil, located in Zungarococha-Loreto. The statistical design was the DBCA, with a duration of 90 days, concluding that, with 40 t / ha of organic fertilizer, the best results were produced in phenology and yield, who presented fruits with an average of 50 g, making a total of 742.75 g / plant and 17,826 Kg / ha, with economic utility of S/.58,253.00.